(untitled) (Revista Argentina de Cirugía, 2021)
Background:The advances in perioperative care and immunosuppressive treatment resulted in a significant increase in survival of transplant patients; as a result, cholelithiasis is more common in transplant patients. Objective: The aim of this study is to analyze and describe the results obtained in cholecystectomies in heart transplant patients. Material and methods: We selected patients by cross-referencing the databases of heart transplantation and scheduled biliary surgeries, and collected information on their medical history, clinical parameters and laboratory tests, among other data. Results: Between January 1994 and December 2017, 154 heart transplant procedures were performed; mean age was 40 years; 16 underwent laparoscopic cholecystectomy after heart transplantation and were included in this study. There were no complications, readmissions or deaths. Conclusion: Laparoscopic cholecystectomy is safe and is the method of choice for heart transplant patients with cholelithiasis. Intraoperative cholangiography should be performed as the predictors of choledocholithiasis are usually abnormal.